2010
DOI: 10.1093/jxb/erq013
|View full text |Cite
|
Sign up to set email alerts
|

Terminal drought-tolerant pearl millet [Pennisetum glaucum (L.) R. Br.] have high leaf ABA and limit transpiration at high vapour pressure deficit

Abstract: It was previously shown that pearl millet genotypes carrying a terminal drought tolerance quantitative trait locus (QTL) had a lower transpiration rate (Tr; g cm−2 d−1) under well-watered conditions than sensitive lines. Here experiments were carried out to test whether this relates to leaf abscisic acid (ABA) and Tr concentration at high vapour pressure deficit (VPD), and whether that leads to transpiration efficiency (TE) differences. These traits were measured in tolerant/sensitive pearl millet genotypes, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
149
1
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(180 citation statements)
references
References 43 publications
22
149
1
8
Order By: Relevance
“…Indeed, under similar environmental conditions, two genotypes with the same leaf area exhibiting differences in leaf canopy conductance would lose different amounts of water. For example, pearl millet genotypes varied with respect to leaf canopy conductance under fully irrigated conditions despite exhibiting a similar leaf area (Kholová et al 2010a), and this appeared to be related to higher leaf ABA content in genotypes with low leaf canopy conductance (Kholová et al 2010b). Similar results were obtained in chickpea (Zaman-Allah et al 2011b) and cowpea (Belko et al 2012), where the canopy conductance differed among genotypes.…”
Section: Leaf Canopy Conductancesupporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, under similar environmental conditions, two genotypes with the same leaf area exhibiting differences in leaf canopy conductance would lose different amounts of water. For example, pearl millet genotypes varied with respect to leaf canopy conductance under fully irrigated conditions despite exhibiting a similar leaf area (Kholová et al 2010a), and this appeared to be related to higher leaf ABA content in genotypes with low leaf canopy conductance (Kholová et al 2010b). Similar results were obtained in chickpea (Zaman-Allah et al 2011b) and cowpea (Belko et al 2012), where the canopy conductance differed among genotypes.…”
Section: Leaf Canopy Conductancesupporting
confidence: 55%
“…Similar results were obtained in chickpea (Zaman-Allah et al 2011b) and cowpea (Belko et al 2012), where the canopy conductance differed among genotypes. In the research reported by Kholová et al (2010b), Zaman-Allah et al (2011b) and Belko et al (2012), the leaf canopy conductance was calculated as the ratio of gravimetric transpiration measurements at the wholeplant level divided by the leaf area and the time that plants were allowed to transpire (either an entire day or one-hour time periods across an entire day). Thus, it was ensured that the leaf area index of the plants was <1, such that there was a lack of (or limited) mutual shading of leaves.…”
Section: Leaf Canopy Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…Alguns trabalhos com soja (Fletcher et al, 2007), sorgo (Gholipoor et al, 2010) e milheto (Kholová et al, 2010) têm mostrado que há variabilidade genética na resposta da transpiração, em diferentes condições de demanda evaporativa da atmosfera. Essas constatações poderiam explicar a variabilidade, obtida no presente trabalho, entre as Figura 3.…”
Section: Resultsunclassified
“…Esse fato poderia levar à limitação do fluxo transpiratório com um conteúdo de água maior no solo, ou seja, poderia resultar em maiores valores de FATS crítica, mas essa hipótese não se confirmou em seu estudo com dois híbridos de milho, que não apresentaram variação significativa nos valores de FATS crítica entre os tratamentos de DPV (11,20,29 e 36 hPa). No entanto, alguns trabalhos indicam que a transpiração aumenta com o aumento do DPV, e que as respostas variam entre espécies e entre genótipos da mesma espécie (Fletcher et al, 2007;Sinclair et al, 2008;Wherley & Sinclair, 2009;Gholipoor et al, 2010;Kholová et al, 2010).…”
Section: Introductionunclassified